HUBUNGAN PELAKSANAAN MASSASE PUNGGUNG PADA IBU BERSALIN DENGAN PENGURANGAN RASA NYERI DALAM PERSALINAN KALA 1 FASE AKTIF DI BPM â€œNâ€ KOTA PADANG PANJANG TAHUN 2014 - Widia Wahyuni, Amy; Ramadhaniati, Fitri Ramadhaniati (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
Childbirth is a series of events which ended with a baby spending enough or nearly enough months followed by the expulsion of the placenta and fetal membranes from the mother's body. Pain in childbirth is a physiological thing caused by stretching of the pelvic floor muscles and stretching of the pelvic floor tissue surrounding the birth canal. This study aims to determine the relationship implementation massase back with reduction of pain in the first stage of labor is the active phase as non-pharmacological measures. Type of research is analytic design with pre-experimental design with one group pretest-posttest design. The population in this study are women giving birth in BPM "N" Padang Panjang Year 2014. The sample included 30 people with a sampling technique that accidental. By using a pain scale measurement sheet first interview (pretest) and the questionnaires measuring pain scale (posttet) after massase backs for 20 minutes. Data are analyzed using t test dependent.Results showed that there is a relationship massase implementation maternal backs on the reduction of pain in the first stage of labor is the active phase (P = 0.000).Most respondents prior to massase backs have moderate category 17 respondents (56.67%) and the weight category 13 respondents (43.33%) and after massase back the majority of respondents in the category of moderate pain and no respondents in the weight category.